Parent routines, child routines, and family demographics associated with obesity in parents and preschool-aged children - Jones, Blake L.; Fiese, Barbara H. (Frontiers in Psychology, 2014)
Many daily routines and behaviors are related to the prevalence of obesity. This study investigated the association between routines and behaviors that act as protective factors related to lower prevalence of obesity in parents (BMI ≥ 30 kg/m2) and overweight in preschool children (BMI ≥ 85th percentile). Socio-demographic characteristics were assessed in relation to protective routines (PRs), and prevalence of obesity/overweight data from 337 preschool children and their parents. The two PRs assessed with parents included adequate sleep (≥ 7 hours/night) and family mealtime routine (scoring higher than the median score). The four PRs assessed in children included adequate sleep (≥ 10 hours/night), family mealtime routine, limiting screen-viewing time (≤ 2 hours/day of TV, video, DVD), and not having a bedroom TV. Overall, 27.9% of parents were obese and 22.8% of children were overweight, and 39.8% of the parents had both parent PRs, and only 11.6% of children had all four child PRs. Results demonstrated that several demographic factors were significantly related to the use of PRs for parents and children. The lack of PRs was related to increased risk for overweight in children, but not for obesity in parents. However, in the adjusted models the overall cumulative benefits of using PRs was not significant in children either. In the multivariate adjusted logistic regression models, the only significant individual PR for children was adequate sleep. In a path analysis model, parent sleep was related to child sleep, which was in turn related to decreased obesity. Overall, findings suggest that parent and child PRs, especially sleep routines, within a family can be associated and may play an important role in the health outcomes of both parents and children. Understanding the mechanisms that influence how and when parents and children use these PRs may be promising for developing targeted family-based obesity-prevention efforts.